The phenomenology of insight: the Aha! experience - Danek, Amory H. (The Routledge international handbook of creative cognition, 2023)
This chapter focuses on the affective component of insight problem solving: The Aha! experience. It represents an attempt to clarify the origin and meaning of this concept and provides the first evidence-based definition of Aha! experiences. Starting with the first historical experiments on thinking, the advantages and disadvantages of the phenomenological approach are discussed. I provide a novel analysis of the original sources by Bühler, who introduced the term Aha! experience, followed by a review of studies that investigated the phenomenology of insight. The available data are summarized for each experiential dimension separately (pleasure, confidence, suddenness, relief, surprise, drive and impasse), aiming to disentangle their unique contribution to Aha! phenomenology. This review identifies pleasure, confidence and subjective suddenness as the three core dimensions that predict Aha! experiences. Influencing factors of Aha! such as solution correctness, solution complexity, patterns of restructuring, feedback and expertise are also discussed. In sum, the current chapter demonstrates the feasibility, importance and usefulness of measuring the phenomenology of insight.